2013
DOI: 10.1128/jvi.03518-12
|View full text |Cite
|
Sign up to set email alerts
|

The VP8* Domain of Neonatal Rotavirus Strain G10P[11] Binds to Type II Precursor Glycans

Abstract: e Naturally occurring bovine-human reassortant rotaviruses with a P[11] VP4 genotype exhibit a tropism for neonates. Interaction of the VP8* domain of the spike protein VP4 with sialic acid was thought to be the key mediator for rotavirus infectivity. However, recent studies have indicated a role for nonsialylated glycoconjugates, including histo-blood group antigens (HBGAs), in the infectivity of human rotaviruses. We sought to determine if the bovine rotavirus-derived VP8* of a reassortant neonatal G10P[11] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
120
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(129 citation statements)
references
References 38 publications
6
120
0
3
Order By: Relevance
“…However, vaccine efficacy remains suboptimal in lowincome settings, where the burden of disease is greatest (13)(14)(15). Recent studies have distinguished HRVs from animal rotaviruses (ARVs) based on their respective receptor usages for initial infection, with most HRVs binding human histo-blood group antigens (HBGAs) and ARVs binding sialylated glycans (16)(17)(18)(19). HBGAs, namely, ABH and Lewis antigens, have been suggested to be genetic factors that determine host susceptibility (20), and both secretor status and Lewis status (regulated by the fucosyltransferase 2 [FUT2] and fucosyltransferase 3 enzymes, respectively) have been proposed to mediate susceptibility to infection and possibly vaccination in a rotavirus genotype-dependent manner (21).…”
mentioning
confidence: 99%
“…However, vaccine efficacy remains suboptimal in lowincome settings, where the burden of disease is greatest (13)(14)(15). Recent studies have distinguished HRVs from animal rotaviruses (ARVs) based on their respective receptor usages for initial infection, with most HRVs binding human histo-blood group antigens (HBGAs) and ARVs binding sialylated glycans (16)(17)(18)(19). HBGAs, namely, ABH and Lewis antigens, have been suggested to be genetic factors that determine host susceptibility (20), and both secretor status and Lewis status (regulated by the fucosyltransferase 2 [FUT2] and fucosyltransferase 3 enzymes, respectively) have been proposed to mediate susceptibility to infection and possibly vaccination in a rotavirus genotype-dependent manner (21).…”
mentioning
confidence: 99%
“…Furthermore, the electrostatic potential surface comparison revealed the similarities and differences among different P genotypes, which may explain to some extent the various binding patterns observed in the functional assays (11,12,(16)(17)(18)36). However, for the potential binding site of P [19], the surface presentation of P [3] and Sia, P [14] and A, P [11] and LNnT, and P [19] showed that there was indeed a cavity in the potential binding site in P [19] VP8* (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…P [11] showed obvious binding to type 1/type 2 precursors (16,17). In addition, P [9], P [14], and P [25] all bound to A type HBGA (A-HBGA) (18).…”
mentioning
confidence: 99%
“…Recent data challenges this view. The VP8* of some human strains have been shown to bind nonsialylated glycans, including histo-blood group antigens (HBGAs) on cell surfaces (Hu et al, 2012;Huang et al, 2012;Liu et al, 2012;Ramani et al, 2013). It appears that interactions with sialoglycans are not an absolute requirement for initial cell attachment for many human rotaviruses, and virus genotype-dependent variations in glycan specificity may have implications for other aspects of rotavirus pathogenesis, such as interspecies transmission.…”
Section: Clinical Illness and Mechanisms Of Pathogenesismentioning
confidence: 96%